IN VITRO INOCULATION OF ASPARAGUS OFFICINALIS TISSUE CULTURE SHOOTS WITH FUSARIUM PROLIFERA TUM - N.A.R. NIK NORULAINI; B. SALLEH; R.A.R. ISKANDAR; A.K. MOHD OMAR (BIOTROPIA, 1999)
ABSTRACT Artificially inoculated asparagus tissue culture plantlets with a virulent fungus,Â  Fusarium proliferatum showed signs of infection as early as 4 days after inoculation. Macroscopic observations revealed presence of early symptoms such as necrotic lesions at the affected area and light microscopic examinations clearly revealed the post-penetration events that took place including the destruction of surrounding cells. However, little is known of the hyphal activity or advancement on the host's surface at the initial stage after inoculation. Scanning electron microscopic examination clearly revealed the hyphal advancement on the surface and the mode of entrance into the host tissues beneath. Four days after inoculation, the fungi proceeded to spread out from the inoculation point onto the host surface which eventually developed into a sparse network of both aerial and non-aerial hyphae. Non-aerial hyphae form a network of mycelium that adheres to the surface and it's movement appeared to be oriented towards the stomata. Hyphal penetration occurs more often through the stomata, natural openings or wounds. In some cases, the hyphae crossed over the stomatal opening without entering the host tissues. At places where the cuticle layer is absent or not well developed the hyphae successfully grew in between the epidermal cells into the tissues beneath. Key words: Tissue culture/Asparagus officinalis/shoots/Artificial inoculstion/Fusarium proliferatum.